Preacher and Scientist: Integration of Science in Law Determination - Egi Sukma Baihaki (Kaunia: Integration and Interconnection Islam and Science, 2018)
Preacher and Scientist are not two different groups (science and profession) that must be disputed. Historically, the Preacher of the classical period also studied, controlling even in themselves they were also a Scientist. Along with the development of the age and science, there is a 'dichotomy' that separates those groups (science and profession). Many events that showed the difference and the conflict between the two groups. Integration of science or inter-profession should be done in every policy, decision, opinions as well as those that are legal products, both legal in general or Islamic law. On the other hand, both groups should be united in overcoming and responding to various problems of life that continue to develop. The integration of science will make the various policies, views and legal products more comprehensive. By using qualitative methods in the form of literature study can be seen that in Islamic history and science have a very close relationship. Fiqh is not a binding and unchanging rigid product. Fiqh must be able to change and synergize with various science disciplines so that various human problems can be answered.